APPLYING THE DISCIPLESHIP PRINCIPLES WITHIN PAUL EXPERIENCE TOWARD DIGITAL DISCIPLESHIP DURING THE COVID-19 PANDEMIC - Warouw, Winda Novita (Klabat Theological Review; Vol 3 No 1 (2022): Klabat Theological ReviewDO - 10.31154/ktr.v3i1.816.34-43, 2022)
The covid-19 pandemic has affected the world in so many ways, and discipleship is not to be excluded from it. Digital discipleship through three main elements (Content Creators, Distributors, and Engagers) is viewed as effective to help the process of discipleship prevail during the challenging time. Before and during the pandemic, the same issues are apparent: the lack of involvement, creativity, and knowledge.  Several crucial aspects can be implemented from the experience of Paul to the present digital discipleship approach. Primarily, the content creators may create Christ-centered content, be aware of people’s challenges and relate it to the content, and make sure that the content will undergo creative development. Moreover, the distributors should be consistent in presenting Christ, deny self in sharing the content, and should go through a spiritual transformation themselves. Lastly, the engagers may implement Jesus’ way of touching lives, be ever-aware of the hardships that may come their way, and always improve their engagement to pursue progress in one’s spiritual life. Keywords: Discipleship, Covid-19   Bibliography Allam, Z. (2020). Surveying the COVID-19 Pandemic and its Implications: Urban Health, Data Technology, and Political Economy . Amsterdam, Netherlands Cambridge, MA: Elsevier. Barton, B. B., & Osborne, G. R. (1999). 1 & 2 Corinthians . Wheaton, Ill.: Tyndale House. Costea, N. (2020).  19 Covid Lessons the Church Cannot Ignore: Why “Back to Normal” Is Not an Option . Evangelista Media. Downey, M. (2000). The New Dictionary of Catholic Spirituality . Collegeville, MN: Liturgical Press. Domm, J. (2020). Digital Discipleship & Evangelism (1st ed.). AdventSource. Elwell, W. A., (1997). Evangelical Dictionary of Biblical Theology (electronic ed.). Grand Rapids: Baker Book House. Evans, A. T. (1997). What Matters Most: Four Absolute Necessities in Following Christ . Chicago: Moody Press Fink, P. E. (2000). The New Dictionary of Sacramental Worship . Collegeville, MN: Liturgical Press. Gorday, L., Village, A.  & Lawson, S. (2020). Impact of Covid-19 on Fragile Churches: Is the Rural Situation Really Different. Rural Theology, 18:2 . Gorday, P. (2000). Colossians, 1-2 Thessalonians, 1-2 Timothy, Titus, Philemon . Downers Grove, Ill.: InterVarsity Press. Hawthorne, G. F., Martin, R. P., & Reid, D. G. (1993). Dictionary of Paul and His Letters . Downers Grove, IL: InterVarsity Press. Hunt, J. (2019). The Digital Way: Re-imagining Digital Discipleship in The Age of Social Media. Journal of Youth and Theology, 18 . Jones, P. (2003). Capturing the Pagan Mind: Paul’s Blueprint for Thinking and Living in the New Global Culture . Nashville, Tenn.: Broadman & Holman. Lea, T. D., & Black, D. A. (2003). The New Testament: Its Background and Message . Nashville, Tenn.: Broadman & Holman Publishers. Terry, J. M., Smith, E. C., & Anderson, J. (1998). Missiology: An Introduction to the Foundations, History, and Strategies of World Missions . Nashville, Tenn.: Broadman & Holman Publishers.